2011
DOI: 10.1002/we.468
|View full text |Cite
|
Sign up to set email alerts
|

A method for defining wind turbine setback standards

Abstract: Setback distances established by regulatory authorities to minimize the probability of blade fragment impact with roads, structures and infrastructure can often have a significant impact on wind farm development. However, these minimum distance requirements typically rely on arbitrary rules of thumb and are not based on a physical or probabilistic analysis of blade throw. The work reported here uses a probabilistic approach to evaluate the effectiveness of current standards and to propose a new technique for d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 4 publications
0
14
0
Order By: Relevance
“…Since their report, there has been a renewed interest in modeling risk, with several authors reporting on analysis of that risk. [5][6][7][8] The state-of-the-art modeling approach is 6 degrees-of-freedom motion of the blade fragments with aerodynamic loading. Simplified models do not match the results of the 6 degrees-of-freedom models; Sørensen 9 showed that drag ballistics do not capture the downwind distance and the range for vacuum ballistics is too far.…”
mentioning
confidence: 99%
“…Since their report, there has been a renewed interest in modeling risk, with several authors reporting on analysis of that risk. [5][6][7][8] The state-of-the-art modeling approach is 6 degrees-of-freedom motion of the blade fragments with aerodynamic loading. Simplified models do not match the results of the 6 degrees-of-freedom models; Sørensen 9 showed that drag ballistics do not capture the downwind distance and the range for vacuum ballistics is too far.…”
mentioning
confidence: 99%
“…This is a result of applying mathematical methods and representations of empirical models. Among those statements, there is the opinion of Rogers, Slegers and Costello [16], who argue to expand the offsets among rows, simultaneously proving that the distances between turbines in a row are of lesser importance. There is a team of Meyers and Meneveau, who are the advocates of a similar model.…”
Section: Wind Turbines For or Against Urbanized Areasmentioning
confidence: 99%
“…Larwood and van Dam reported on the history of this risk and the modeling of rotor fragments in the context of safety setbacks for wind turbines. Since their report, there has been a renewed interest in modeling, with several authors reporting on fragment analysis . The state‐of‐the‐art modeling approach is six degrees‐of‐freedom (6DOF) motion of the blade fragments with aerodynamic loading.…”
Section: Introductionmentioning
confidence: 99%